Obtaining new Ruscus products using Gamma radiation - Yaarit Kutsher; Nir Hazenshprung; Orit Amir-Segev; Lianne Merchuk-Ovnat; Dalia Evenor; Moshe Reuveni (Ornamental Horticulture, 2020)
Ruscus is an evergreen shrub that offers dark-green glossy foliage used as green additions to bouquets and flower arrangements. One of the most significant ways to obtain new varieties of crop and ornamental plants is to induce mutations by radiation. Gamma radiation is most commonly used to obtain mutants in commercial food as well as feed crops and ornamental plants. In this study, we developed tissue culture methods for Ruscus proliferation from rhizomes to obtain rhizomes clusters. These clusters were subsequently irradiated with Gamma rays to obtain unique phenotypes, such as: elongated narrow phylloclades modified stem symmetry and dwarfed growth habit. Such Ruscus types can contribute to the expansion of the floral industry.